Sabar sebagai Resiliensi Spiritual: Analisis Tafsir QS. Al-Baqarah 155-157 dalam Perspektif Psikologi Islam - Il Maknun, Lu’luk (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to examine the concept of patience in the Qur'an and its relationship to resilience from an Islamic psychology perspective. The focus of this study is an analysis of Surah Al-Baqarah, verses 155–157, which describes various forms of life's trials and patience as a spiritual response to them. Using qualitative methods through a library approach, this study examines various sources, such as the interpretations of Al-Azhar and Al-Munir, as well as Islamic psychology literature and the resilience theory by Connor and Davidson. The results of the study indicate that patience in Islam is not merely a passive attitude toward trials, but rather a form of spiritual strength that actively maintains emotional, mental, and behavioral stability. The values of patience taught in the Qur'an are strongly relevant in developing resilience, namely the ability of individuals to recover from adversity and persist in the face of life's pressures. This study confirms that the integration of faith values, such as patience, is an important foundation for strengthening mental resilience from an Islamic psychology perspective